(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the meanings of the concept of “dua” in explanatory dictionaries as well as its social, religious, and linguistic features. The study discusses dua in singular and plural forms, directed to oneself and to others, with an emphasis on markers of personhood, temporality, and locality. Based on folklore and religious narratives, the power of supplication, its acceptance, and the importance of gratitude are illustrated. The research concludes that dua, as a speech genre, represents a holistic linguistic phenomenon shaped by purpose, style, and composition.